1996
DOI: 10.1148/radiology.200.1.8657921
|View full text |Cite
|
Sign up to set email alerts
|

Indirect MR arthrography: optimization and clinical applications.

Abstract: Indirect MR arthrography of an exercised joint provides homogeneous enhancement and improved delineation of soft-tissue structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
10

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 0 publications
1
52
1
10
Order By: Relevance
“…The contrast agent will distribute into the joint, enhancing synovial fluid and providing greater contrast as well as distension of the capsule, allowing for the interpretation of labrum and cartilage. 49,[57][58][59][60][61] In one study comparing i-MRA and d-MRA, i-MRA showed a sensitivity of 88% and an accuracy of 90%. 62 Byrd et al demonstrated that D-MRA was much more sensitive in the detection of various lesions, however, arthroscopy demonstrated that d-MRA was interpreted falsely positive twice as much compared to i-MRA ( Figure 7).…”
Section: Labrummentioning
confidence: 99%
“…The contrast agent will distribute into the joint, enhancing synovial fluid and providing greater contrast as well as distension of the capsule, allowing for the interpretation of labrum and cartilage. 49,[57][58][59][60][61] In one study comparing i-MRA and d-MRA, i-MRA showed a sensitivity of 88% and an accuracy of 90%. 62 Byrd et al demonstrated that D-MRA was much more sensitive in the detection of various lesions, however, arthroscopy demonstrated that d-MRA was interpreted falsely positive twice as much compared to i-MRA ( Figure 7).…”
Section: Labrummentioning
confidence: 99%
“…Este princípio é usado nos estudos por artrografia indireta pela RM, em que, após a injeção do meio de contraste endovenoso e movimentação ativa da articulação em estudo, obtêm-se imagens com líquido articular contendo o contraste paramagnético que atravessa rapidamente a membrana sinovial, chegando no espaço articular (31,33,34) . Em nossos pacientes, uma simples caminhada até o local do exame poderia aumentar a permeabilidade vascular no quadril, mesmo antes Uma outra explicação para esta alteração sinovial seria a correlação com a fase angiogênica do processo inflamatório na AR, em que, histologicamente, há uma hiperplasia da membrana sinovial com proliferação dos linfócitos perivasculares, do tecido necrótico e proliferação das células T e B, sem promover sintomas ao paciente, um estágio que precederia a proliferação sinovial propriamente dita, em que o paciente já apresenta quadro clínico de dor, edema e rigidez matinal, além da caracterização da sinovite pela RM, ultrasonografia ou mesmo a cintilografia (35) .…”
Section: Discussionunclassified
“…Hence, although MRA is not advocated at some centres, many authors suggest MRA as a useful tool to help image the post-operative patient successfully. [8][9][10] CT plays an important role in identifying the position of the sutures and evaluating the osseous structures in the postoperative shoulder. CTA is an alternative to MRI and MRA.…”
Section: Imaging Approachmentioning
confidence: 99%
“…contrast, but in our experience, the use of indirect CTA is limited to the detection of synovitis. 8 Ultrasonography is an excellent alternative modality for evaluating the post-operative rotator cuff, because it is not subject to artefact from metallic implants. 15 Prickett et al 16 showed that ultrasonography has a sensitivity of 91%, a specificity of 89% and an accuracy of 89% for identifying rotator cuff integrity after surgery.…”
Section: Imaging Approachmentioning
confidence: 99%